Surgical Versus Nonsurgical Interventions to Relieve upper Airway Obstruction in Children with Pierre Robin Sequence. Issue 3 (2015) - Kam, Karen; McKay, Meghan; MacLean, Joanna; Witmans, Manisha B; Spier, Sheldon; Mitchell, Ian
Abstract : BACKGROUND: Newborns with Pierre Robin sequence (PRS) often experience chronic intermittent hypoxemia/hypoventilation associated with airway obstruction. The heterogeneity of the severity of upper airway obstruction makes management a challenge; the optimal intervention in individual cases is not clear. OBJECTIVE: To investigate the prevalence of surgical/nonsurgical interventions for PRS at two children's hospitals. Patient characteristics and outcomes were examined. METHODS: The present retrospective chart review identified 139 patients with PRS born between 2000 and 2010. Demographic information, mode of airway management, associated anomalies and syndromes, polysomnography results, length of intensive care unit and hospital stay, complications and deaths were extracted. RESULTS: Interventions included prone positioning (alone [61%]), tongue-lip adhesion (45%), nasopharyngeal intubation (28%), continuous positive airway pressure (20%), tracheostomy (19%) and mandibular distraction osteogenesis (5%). Tracheostomies were more prevalent in syndromic patients (P=0.03). Patients who underwent tracheostomy had a lower birth weight (P=0.03) compared with newborns with other interventions. Patients who underwent surgical interventions had longer intensive care unit stays (P<0.001). No intervention was associated with a statistically significant likelihood of requiring a subsequent intervention. Thirty percent of patients underwent polysomnography, with a higher proportion of these using continuous positive airway pressure (n=15) (P<0.01). CONCLUSIONS: In the present descriptive study, patients with syndromic PRS or low birth weight underwent early intervention, which included a tracheostomy. Objective measures of airway obstruction were underutilized. Decision making regarding evaluation and management of upper airway obstruction in this population remains clinician and resource dependent. Reporting data obtained from a large cohort of PRS patients is important to compare experiences and motivate future studies investigating this complex condition.